PENGARUH PELAKSANAAN PENDAMPINGAN KADER TERHADAP KUNJUNGAN ANTENATAL CARE (ANC) IBU HAMIL RESIKO TINGGI DI MEGALUH JOMBANG - Kolifah Kolifah (Jurnal Ilmiah Kesehatan, 2017)
The maternal mortality rate (MMR) in Indonesia as one of the adult health indicators are still high when compared with other countries in ASEAN. Every pregnant women face the risk of death, so that the necessary efforts to improve the health status of pregnant women to maternity, is mentoring by volunteers. This study aims to investigate the influence implementation of assistance cadres to visit antenatal care (ANC) pregnant women at high risk. Research is correlational design with cross sectional approach. The subject of the study 29 pregnant women at high risk SPR score ≥10 at second and third trimester pregnancy. The independent variable is the duty of cadres as facilitator, motivator, and mediator were obtained by interview and notebook cadres. The dependent variable is the ANC of books KIA pregnant women. Analyzed by frequency distribution, bivariate with a person product moment test, and multivariate logistic regression. The majority of cadres as active facilitator (63%), almost entirely as an active motivator (86%), almost entirely as an active mediator (83%) and were mostly as a companion active (83%). ANC high-risk pregnant women the majority (66%) regularly. There is a mutual effect equally between tasks ANC cadres to visit pregnant women at high risk. The most influential is the duty of cadres as a companion. Community involvement ie cadres, community leaders and religious leaders in implementing health programs are required to enable achievement of the health targets can be maximized.